Handbook for Evaluating Infrastructure Regulatory Systems - Brown, Ashley C. (Washington, DC: World Bank, 2012)
More than 200 new infrastructure regulators have been created around the world in the last 15 years. They were established to encourage clear and sustainable long-term economic and legal commitments by governments and investors to encourage new investment to benefit existing and new customers. There is now considerable evidence that both investors and consumers-the two groups that were supposed to have benefited from these new regulatory systems-have often been disappointed with their performance. The fundamental premise of this book is that regulatory systems can be successfully reformed only if there are independent, objective and public evaluations of their performance. Just as one goes to a medical doctor for a regular health checkup, it is clear that infrastructure regulation would also benefit from periodic checkups. This book provides a general framework as well as detailed practical guidance on how to perform such regulatory checkups.